Red state blues how the conservative revolution stalled in the states - Grossmann, Matthew 1979- (Cambridge University Press, 2019)
Over the last quarter century, a nationalized and increasingly conservative Republican Party made unprecedented gains at the state level, winning control of twenty-four new state governments. Liberals and conservatives alike anticipated far-reaching consequences, but what has the Republican revolution in the states achieved? Red State Blues shows that, contrary to liberals' fears, conservative state governments have largely failed to enact policies that advance conservative goals or reverse prior liberal gains. Matt Grossmann tracks policies and socioeconomic outcomes across all 50 states, interviews state insiders, and considers the full issue agenda. Although Republicans have been effective at staying in power, they have not substantially altered the nature or reach of government. Where they have had policy victories, the consequences on the ground have been surprisingly limited. A sober assessment of Republican successes and failures after decades of electoral victories, Red State Blues highlights the stark limits of the conservative ascendancy